Formation of multimers of bacterial collagens through introduction of specific sites for oxidative crosslinking. Issue 9 (26th May 2016) - Stoichevska, Violet; An, Bo; Peng, Yong Y.; Yigit, Sezin; Vashi, Aditya V.; Kaplan, David L.; Werkmeister, Jerome A.; Dumsday, Geoff J.; Ramshaw, John A. M.
Abstract: A range of non‐animal collagens has been described, derived from bacterial species, which form stable triple‐helical structures without the need for secondary modification to include hydroxyproline in the sequence. The non‐animal collagens studied to date are typically smaller than animal interstitial collagens, around one quarter the length and do not pack into large fibrillar aggregates like those that are formed by the major animal interstitial collagens. A consequence of this for biomedical products is that fabricated items, such as collagen sponges, are not as mechanically and dimensionally stable as those of animal collagens. In the present study, we examined the production of larger, polymeric forms of non‐animal collagens through introduction of tyrosine and cysteine residues that can form selective crosslinks through oxidation. These modifications allow the formation of larger aggregates of the non‐animal collagens. When Tyr residues were incorporated, gels were obtained. And with Cys soluble aggregates were formed. These materials can be formed into sponges that are more stable than those formed without these modifications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2369–2376, 2016.